Las competencias ciudadanas desde el seminario interdisciplinar diversofía: una sistematización de experiencias (2020)
The purpose of the research was to systematize the Diversofía Interdisciplinary Seminar (SID) that has been developed at the San Bernardino IED School in the city of Bogotá, between 2019 and 2020 with vocational media students. It focuses on the contributions of the Seminar in terms of the development of citizenship skills of its participants. The question that guided the systematization was how did the SID contribute to the development of citizenship competencies with the vocational media students of the San Bernardino School during 2019 and 2020? To answer the central question, a qualitative research framed within the hermeneutical paradigm and a methodology for systematizing experiences was carried out, which had five stages. In the first, guiding questions were formulated for the entire process. In the second, the collection of records such as curricular meshes, personal class notes, photographs and student learning products was included. In the third, the implementation of semi-structured interviews with seven teachers, a focus group and a survey of a group of students was carried out, this with the aim of reconstructing the process experienced in the SID. In the fourth stage, a critical interpretation of the experiences was carried out, through an exercise of categorization and triangulation of the information, the purpose of which was to establish the scope of the SID in the development of citizen competencies. In the fifth stage, the general conclusions and recommendations of the investigation were proposed. As results of the investigation, it was determined through some implemented strategies that the SID achieved the basic development of citizen competencies.